Factors influencing students’ information channel preferences in finding sources for their final academic reports - Muliyadi, Irvan (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. Understanding students' information channel preferences for information sources in academic tasks is crucial for improving library services. This study identifies factors influencing these preferences. Data Collection Methods. Data were gathered through semi-structured interviews with 26 final-year students working on their theses, focusing on their selection of information channels. Data Analysis. The interview results were transcribed verbatim and analyzed thematically. Recurring themes were identified and categorized based on participants' responses, revealing common preferences for information sources. Results and Discussion. This study found that factors influencing the choice of information sources include the convenience, quantity, and quality of information sources provided by different channels. Additionally, users’ intentions, such as the need to obtain specific types of academic sources or the desire to personally own the acquired sources, also play a significant role. Therefore, academic libraries should ensure that their services are created, maintained, and developed based on users' experiences with existing library services to better meet their academic information needs and support them in completing their academic tasks. Conclusion. In today's academic world, students have diverse preferences for where they find information. Some lean towards the library, while others prefer the internet, especially for their final projects. Interestingly, some see both as useful for their research.